Exploring the Intersection of Cultural Heritage Preservation and Digital Humanities: Case Studies from Global Perspectives - Taseer, Muhammad (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2024)
In today's digital era, the intersection of cultural heritage preservation and digital humanities has become increasingly significant. This study aims to explore this intersection through a qualitative analysis of case studies from global perspectives. Utilizing methods such as literature review, library research, and qualitative analysis, this research delves into the various ways in which digital technologies are employed to preserve and promote cultural heritage worldwide. The study examines the challenges, opportunities, and ethical considerations associated with the digitization and dissemination of cultural artifacts, monuments, and traditions. By analyzing case studies from diverse geographical and cultural contexts, this research sheds light on the innovative approaches and best practices in the field of cultural heritage preservation within the realm of digital humanities. The findings of this study contribute to a deeper understanding of the complex relationship between technology and culture, highlighting the role of digital humanities in safeguarding and revitalizing cultural heritage for future generations.